Hope Harbor: Sandcastle Inn - Book 10 - Hannon, Irene (Thorndike, Maine : Center Point Large Print, 2024)
"Vienna Price never intended to return for more than a passing visit to Oregon and all the bad memories shed left behind. But when your career tanks, home is where you go to nurse your wounds and chart a new course. Only temporarily, of course -- because as much as she loves her quirky mom, anything more than a short stay would drive them both crazy. A trip to Oregon isnt in Matt Quinns plans, either, until a perfectly timed appeal for help arrives from his sister. What better place to decompress after a shattering loss than a quiet, seaside town named Hope Harbor? But R&R isnt on the agenda when he arrives to find his sisters new enterprise on life support. Vienna, however, may have just the skills needed to resuscitate the foundering B&B -- if Matt can convince her to hang around long enough to mend an inn . . . and his heart."--
Keywords: Life change events -- Fiction; Man-woman relationships -- Fiction; Bed and breakfast accommodations -- Fiction; Small cities -- Oregon; Fiction; Oregon -- Fiction; Christian fiction; Romance fiction; Large print books